PERAN UNI EROPA DALAM MENANGANI KRISIS EKONOMI STUDI KASUS : KRISIS EKONOMI PERBANKAN DAN DEFISIT ANGGARAN IRLANDIA TAHUN 2008-2011 - , REZA FEBRIZA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As one of the largest regionalism in the world, the European Union has a duty to provide help member countries that are affected by the problem in a variety of sectors, including in the economic sector. Ireland is one of the countries in the EU are affected by the global economic crisis in 2008, which the growth of the Irish economy continued to decline sharply due to the global economic crisis of 2008. As a regionalism that overshadow Ireland, the European Union has a duty to help Ireland out of the economic crisis and restore growth in the Irish economy grew rapidly. One mechanism that is run by the European Union is to establish EFSM, a mechanism to overcome the problems Irish economic crisis. This mechanism is expected to be able to help solve the problems of the economic crisis in Ireland and return the Irish to be one of the fastest growing economies in the European Union. This mechanism will be established an agreement between the Irish with the European Commission by Irish and European Central Bank to create targets to be achieved by Ireland for getting financial assistant from the European Commissio